1997
DOI: 10.1177/10454411970080030201
|View full text |Cite
|
Sign up to set email alerts
|

Is Fibroblast Heterogeneity Relevant To the Health, Diseases, and Treatments of Periodontal Tissues?

Abstract: There are wide variations of gene expression and strikingly different responses to extracellular signals among different fibroblast populations. This has prompted a large number of in vitro studies which suggest that fibroblasts are not homogeneous but instead comprise multiple subpopulations with extensive site-to-site and intra-site variations. Conceivably, either fibroblasts are not all created equal, or, alternatively, discrete subpopulations may emerge in development, inflammatory lesions, or wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 117 publications
1
91
0
3
Order By: Relevance
“…Oral mucosa comprises stratified squamous epithelium, and its underlying connective tissue harbours various mesenchymal cells such as fibroblasts, endothelial cells, and pericytes [1,2] . These cells and their extracellular matrix (ECM) play pivotal roles in cell differentiation and proliferation during tissue development, wound healing processes, and pathological alterations [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…Oral mucosa comprises stratified squamous epithelium, and its underlying connective tissue harbours various mesenchymal cells such as fibroblasts, endothelial cells, and pericytes [1,2] . These cells and their extracellular matrix (ECM) play pivotal roles in cell differentiation and proliferation during tissue development, wound healing processes, and pathological alterations [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with other resident cell types, these cells are responsible for maintaining the structural integrity of the periodontium, as well as facilitating the repair and/or regeneration of these tissues following injury (Lekic et al, 1997). We recently showed that fibroblasts derived from human periodontal ligament (HPLFs) did not display growth inhibition, cellcycle arrest or dsDNA damage typically associated with CDT (Kanno et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…F ibroblasts and their extracellular matrix products play pivotal roles in maintaining the structural integrity of connective tissues, in healing processes, and in pathological alterations (1,2). Fibroblasts are not a homogeneous population in different anatomical regions or even within a single tissue, and are considered to actively define the structure of microenvironments and modulate immune cell behavior by conditioning the local and cellular microenvironment (1,2).…”
mentioning
confidence: 99%
“…Fibroblasts are not a homogeneous population in different anatomical regions or even within a single tissue, and are considered to actively define the structure of microenvironments and modulate immune cell behavior by conditioning the local and cellular microenvironment (1,2). Human gingival fibroblasts (HGF), 3 the major constituent of gingival connective tissue, have been shown to express immunologic receptors, such as a bacterial pattern recognition receptor CD14 (3,4), TLRs (5), and costimulatory molecule CD40 (1,6) and to produce various cytokines, such as IL-1, IL-6, IL-8, and MCP-1, by interaction with their ligands (3)(4)(5)7).…”
mentioning
confidence: 99%